Undiagnosed Depression in Spanish-Speaking Latinas Exposed to Intimate Partner Violence. Issue 4 (October 2016) - DiCorcia, Daley; Stein, Sara F.; Grogan-Kaylor, Andrew; Galano, Maria M.; Clark, Hannah; Graham-Bermann, Sandra A.
Depression causes impairment worldwide and disproportionately affects women, Latinos, and those who have experienced intimate partner violence (IPV). This study assessed the prevalence of depressive symptoms among 96 Latinas exposed to IPV. While 85% of women reported clinical-level depression symptoms, only 11% had ever received a diagnosis of depression. Results indicate that greater income, injury, and depression symptoms significantly differentiated women who were diagnosed with depression from those with self-reported clinical-level depression symptoms. Undiagnosed depression is a major public health problem for low-income Latinas exposed to IPV and thus calls for the assessment of this disorder among those with limited access to care.